In pursuit of a sensitive EEG functional connectivity outcome measure for clinical trials in Alzheimer's disease. Issue 1 (January 2020) - Briels, C.T.; Stam, C.J.; Scheltens, P.; Bruins, S.; Lues, I.; Gouw, A.A.
Highlights: Aim was to find a sensitive functional connectivity measure for trials in Alzheimer's disease (AD). The functional connectivity measures phase lag index (PLI) and amplitude envelope correlation with leakage correction (AEC-c) were compared in the SAPHIR trial in early AD. AEC-c may be a sensitive measure to detect treatment effects in clinical trials in AD. Abstract: Objective: In clinical trials in Alzheimer's Disease (AD), an improvement of impaired functional connectivity (FC) could provide biological support for the potential efficacy of the drug. Electroencephalography (EEG) analysis of the SAPHIR-trial showed a treatment induced improvement of global relative theta power but not of FC measured by the phase lag index (PLI). We compared the PLI with the amplitude envelope correlation with leakage correction (AEC-c), a presumably more sensitive FC measure. Methods: Patients with early AD underwent 12 weeks of placebo or treatment with PQ912, a glutaminylcyclase inhibitor. Eyes-closed task free EEG was measured at baseline and follow-up (PQ912 n = 47, placebo n = 56). AEC-c and PLI were measured in multiple frequency bands. Change in FC was compared between treatment groups by using two models of covariates. Results: A significant increase in global AEC-c in the alpha frequency band was found with PQ912 treatment compared to placebo ( p = 0.004, Cohen's d = 0.58). The effect remained significant when corrected for sex, country, ApoE ε4 carriage, age, baseline value (model 1; p = 0.006) and change in relative alpha power (model 2; p = 0.004). Conclusions: Functional connectivity in early AD, measured with AEC-c in the alpha frequency band, improved after PQ912 treatment. Significance: AEC-c may be a robust and sensitive FC measure for detecting treatment effects.